Reactions of Cp*Ir(CO)2 with pentafluorobenzonitrile : half-sandwich iridium complexes Cp*Ir(CO)(p-C6F4CN)(X) - Mak, Garvin Kar Hang (2014)
The reaction of Cp*Ir(CO)2 (1) with pentafluorobenzontrile in the presence of a base afforded the diaryl complex Cp*Ir(CO)(p-C6F4CN)2 (4). The reaction proceeds via the metallacarboxylic acid Cp*Ir(CO)(p-C6F4CN)(COOH) (2). The latter can be decarboxylated in the presence of a base to the hydrido species Cp*Ir(CO)(p-C6F4CN)(H) (5), which can then undergo hydride–chloride exchange to Cp*Ir(CO)(p-C6F4CN)(Cl) (6a). In the presence of air and water, the reaction of 1 with pentafluorobenzontrile afforded a complex formulated as Cp*Ir(CO)(p-C6F4CN){C(OH)(NH2)C6F5} (7a); this is also available from the reaction of 2 with pentafluorobenzamide in the presence of aqueous NaOH.